The ocean's menace - Rutledge, Archibald, 1883-1973 (University of South Carolina Press, 2018)
"One of the more underappreciated aspects of Archibald Rutledge's varied and prolific literary efforts focuses on the way he could weave stories involving danger in the wilds. What he frequently described as chimeras--great sharks, alligators, rattlesnakes, and cottonmouths of incredible and often embellished dimensions, wild hogs with razor-sharp tusks, and more--clearly fascinated him. Similarly, he exhibited a knack for twists and turns in his tales reminiscent of O. Henry at his best. The Ocean's Menace offers a fine example of this aspect of Rutledge as a creative writer. The title is misleading, because it immediately conjures images of something massive, such as a white shark, devilfish, whale, or other leviathan. Instead, "The Ocean" is a remote, treacherous tract of land near Hampton where hunters dared not venture and which locals viewed with a mixture of awe and alarm. It provides an ideal setting for this tale. Rutledge was at his best when writing of whitetails, because deer hunting is woven as a bright thread through the entire fabric of his life. Here though, instead of yet another tale of a mighty stag or an antlered giant, the quarry proves to be the hunter's salvation. Delightfully told, with an abundance of twists and turns as the story unfolds, this is the sage of the Santee at his finest. A project of the Humanities Council SC benefiting South Carolina literary programs, this new edition of The Ocean's Menace is illustrated in handsome charcoal etchings by Southern artist Stephen Chesley. Award-winning outdoors writer and noted Rutledge scholar Jim Casada provides the volume's introduction and afterword."--